Cryosurgery and curettage‐cryosurgery for basal cell carcinomas of the mid‐face. (29th October 2014) - Samain, A.; Boullié, M.C.; Duval‐Modeste, A.B.; Joly, P.
Abstract Background Surgical treatment of basal cell carcinoma (BCC) can be technically difficult in mid‐face area. Cryosurgery is proposed for low‐risk BCC. Cryosurgery has been poorly investigated in mid‐face BCC, which is considered as having a high risk of recurrence. Objective To assess the results of cryosurgery and curettage‐cryosurgery in patients with mid‐face BCC. Methods A retrospective study was performed between 2005 and 2012 in a reference centre for cryosurgery. Inclusion criteria were: (i) diagnosis of BCC confirmed histologically; (ii) location in the mid‐face area; (iii) treatment with cryosurgery performed between August 2005 and December 2010; and (iv) minimal follow‐up of 18 months after cryosurgery. Follow‐up data were recorded until April 2012. Curettage was performed before cryosurgery in 55 cases of nodular BCC (38%). Patients were followed after cryosurgery either by a dermatologist (n = 48) or by their general practitioner (n = 90). Twelve patients were lost to follow‐up. Results One hundred and thirty‐eight patients of mean age 76.5 ± 11.1 years, with a total of 144 BCCs were included. Mean follow‐up was 40.7 ± 15.6 months. Wound healing occurred after a median delay of 4 weeks (range 1–12 weeks). No severe complications were recorded. Seven recurrences (4.9%) were observed after a median time of 24 months (range 4–36 months). The 5‐year Kaplan–Meier recurrence‐free rate was 94%. Thirteen patients with previously treated BCC or morpheiform BCC were treated with cryosurgery as palliative indication, although their subtypes of BCC were theoretical contraindications to cryosurgery. When excluding this subgroup, the 5‐year Kaplan–Meier recurrence‐free rate of the rest of the population was 96.5%. Conclusion Cryosurgery and curettage‐cryosurgery can be considered as an alternative and simple method for treatment of BCC of the mid‐face area.